Diurnal Rhythmicity Programs of Microbiota and Transcriptional Oscillation of Circadian Regulator, NFIL3 - Kubo, Masato (Frontiers in Immunology, 2020)
Circadian rhythms are a very exquisite mechanism to influence on transcriptional levels and physiological activities of various molecules that affect cell metabolic pathways. Long-term alteration of circadian rhythms increases the risk of cardiovascular diseases, hypertension, hypertriglyceridemia, and metabolic syndrome. A drastic change in dietary patterns can affect synchronizing the circadian clock within the metabolic system. Therefore, the interaction between the host and the bacterial community colonizing the mammalian gastrointestinal tract has a great impact on the circadian clock in diurnal programs. Here, we propose that the microbiota regulates body composition through the transcriptional oscillation of circadian regulators. The transcriptional regulator, NFIL3 (also called E4BP4) is a good example. Compositional change of the commensal bacteria influences the rhythmic expression of NFIL3 in the epithelium, which subsequently controls obesity and insulin resistance. Therefore, control of circadian regulators would be a promising therapeutic target for metabolic diseases.